Effects of erythropoietin abuse on exercise performance - Sgrò, P.; Sansone, M.; Sansone, A.; Romanelli, F.; Di Luigi, L. (The Physician and Sportsmedicine, 2018)
The present review provides a comprehensive overview on the erythropoietic and non-erythropoietic effects of rHuEpo on human sport performance, paying attention to quantifying numerically how rHuEpo affects exercise performance and describing physiological changes regarding the most important exercise variables. Much attention has been paid to treatment schedules, in particular, to assess the effects of microdoses of rHuEpo and the prolonged effects on sport performance following withdrawal. Moreover, the review takes into account non-erythropoietic ergogenic effects of rHuEpo, including cognitive benefits of rHuEpo. A significant increase in both Vo2max and maximal cycling power was evidenced in studies taken into account for this review. rHuEpo, administered at clinical dosage, may have significant effects on haematological values, maximal and submaximal physiological variables, whereas few reports show positive effects on exercise perfomance. However, the influence of micro-dose rHuEpo on endurance performance in athletes is still unclear and further studies are warranted.